Acceptability of mHealth Technology for Self‐Monitoring Eating and Activity among Rural Men. Issue 2 (18th October 2016) - Eisenhauer, Christine M.; Hageman, Patricia A.; Rowland, Sheri; Becker, Betsy J.; Barnason, Susan A.; Pullen, Carol H.
Abstract: Objective: To examine rural men's use and perceptions of mobile and wireless devices to self‐monitor eating and physical activity (mHealth). Design and Sample: Men in this 3‐week pilot study used FitBit One ® to log daily food intake and monitor activity. A companion application (app) allowed activity monitoring of fellow participants. Health‐related text messages were received 1–3 times daily. A purposive sample of 12 rural men (ages 40–67) was recruited by community leaders. Measures: (1) baseline heart rate, blood pressure, and BMI, (2) FitBit One ® usage, (3) investigator‐generated surveys on acceptability of mHealth, and (4) focus group on experience with mHealth. Results: Men were overweight ( n = 3) or obese ( n = 9) and 9 of 12 were hypertensive. Nine of twelve wore FitBit One ® all 21 days. Eleven of 12 men logged food, with 9 of 12 doing this at least 15 of 21 days. Self‐monitoring and daily text messaging increased awareness of energy intake and output. Companion app's food log needed targeting for rural foods. Rotating seasons (occupational, religious, recreational) and weak cellular signals created contextual barriers to self‐monitoring eating and activity. Conclusions: FitBit One ® and text messaging were perceived as useful among the rural men, while the companion apps require adaptation to reflect dietary norms.